Handbook of vacuum science and technology - Hoffman, Dorothy M.; Singh, Bawa; Thomas, John H. (Academic Press, 1998)
The Handbook of Vacuum Technology consists of the latest innovations in vacuum science and technology with a strong orientation towards the vacuum practitioner. It covers many of the new vacuum pumps, materials, equipment, and applications. It also details the design and maintenance of modern vacuum systems. The authors are well known experts in their individual fields with the emphasis on performance, limitations, and applications rather than theory. There aremany useful tables, charts, and figures that will be of use to the practitioner.